Esofagectomia na perfuração esofágica com diagnóstico tardio - Andrade,Aderivaldo Coelho de (2007)
Esophageal perforations are related to high mortality rates, especially if there is a delayed diagnostic and treatment. We report an esophageal perforation caused by caustic ingestion, in a suicidal attempt, successfully treated by esophagectomy after a long period of misdiagnosis that lead to infectious complications.